Diagnóstico in vivo de la sarcosistiosis en alpacas utilizando la técnica flotación de esporoquistes - Bautista Bautista, Henry Gabriel (2017)
The research Diagnosis in vivo the sarcocistiosis in the Huasillama alpaquero production system in the Cotopaxi Province, with the objective of identifying the parasite Sarcocystis spp, in local alpacas since this parasite affects the sustainability and sustainability of this production system. The alpaquero production has been decreasing because of the lack of technical contribution, lack of research in the field, lack of investment in research technology to sustain and increase production rates, it is for this reason that the presence of the parasite affects the animal causing great economic losses in both meat production and derivatives as well as in fiber production. The methodology used in the execution of the work and elaboration of tests Sporoquist flotation was performed in 40 alpacas from which fecal samples were extracted directly from the rectum and deposited in sterile containers which arrived at the laboratory following the protocol of transport of samples for thus developing the technique of identification of Sarcocystis spp, in the " ANIMALAB Clinical Diagnostic Laboratory " in the Machachi City. In the results obtained in the investigation was determined that 39 are negative and 1 is positive to the presence of the parasite, resulting in that 2.5% positive to the presence of the parasite which does not represent significant results at the time of the verification of results, since the percentage of positive and analyzed samples is very low in relation to the presence of the parasite during a postmortem diagnosis. Concluding that the use of the esporoquistes flotation technique for the in vivo identification of Sarcocystis spp, is not relevant to make a diagnosis, there are no significant results that reflect in the research.